Exploration of Work Performance of Teachers at Driving Schools - Dian Yulita Sari, Dewa Ayu; Suryadinatha Gorda, Oka (Dinasti Publisher, 2025)
Transformative Schools are educational transformations that focus on holistic student learning outcomes that include competencies consisting of literacy, numeracy, and character development. Many factors determine the progress of education in Indonesia, one of which the biggest is how to develop the potential of human resources (HR), in this research case study the educator, not only will determine the educational process, but also the character transferred from an educator to students will produce a golden generation, amid the decline in character in students in generation Z today. One of the things launched by the current government is the 'Merdeka Belajar' Program. Is one of the methods or ways carried out by the government or in this case, the Ministry of Education and Culture, Research and Technology to provide the widest possible opportunity for students to be able to explore their abilities in many ways, through 6-8 activities that can be followed while sitting in learning activities at school. Students are taught to be able to know, and be attractive in developing themselves, and be sensitive to changes in the environment, society, and all activities outside of school. Of course, the goal is to develop the potential of children or students. By using qualitative methods to determine how much impact the Transformative School has on students' self-development in particular, the data is described in a comprehensive qualitative Descriptive research table.